Gene expression profiling identifies the role of Zac1 in cervical cancer metastasis - Hui-Chen Su (Nature Portfolio, 2020)
Abstract The zinc-finger protein which regulates apoptosis and cell cycle arrest 1 (Zac1), encoded by Plagl1 gene, is a seven-zinc-finger containing transcription factor belonging to the imprinted genome and is expressed in diverse types of embryonic and adult human tissues. Zac1 is postulated to be a tumor suppressor by inducing cell cycle arrest and apoptosis through interacting and modulating transcriptional activity of p53 as it was named. Correspondingly, the reduction or loss of Zac1 expression is associated with the incidence and progression of several human tumors, including cervical cancer, breast cancer, ovarian cancer, pituitary tumors, and basal cell carcinoma, implying the rationality of utilizing Zac1 expression as novel a biomarker for the evaluation of cervical cancer prognosis. However, to date, it has not been elucidated whether Zac1 expression is related to the prognosis of patients in clinical cervical cancer tumor samples. To address the questions outlined above, we report here a comprehensive investigation of Zac1 expression in biopsies of clinical cervical carcinoma. By analyzing Zac1 expression in various gene expression profiling of cervical cancer databases, we show the association between high Zac1 expression and poor prognosis of cervical cancer. Functional enrichment analysis showed that high Zac1 expression was associated with epithelial-mesenchymal transition (EMT), which was further observed in clinical characteristics and metastatic carcinoma samples using immunohistochemical staining. Correspondingly, hypomethylation of CpG island on Zac1 promoter was observed in samples with high Zac1 expression in cervical carcinoma. Finally, overexpression of Zac1 in a variety of cervical cancer cell lines increase their mesenchymal biomarker expression and migration, strengthening the correlation between cervical cancers with high Zac1 expression and metastasis in clinical. In summary, this research firstly revealed that identifying Zac1 expression or the methylation status of CpG site on Zac1 promoter may provide us with novel indicators for the evaluation of cervical cancer metastasis.